A Critique on the Book Immanuel Kant - Mazdak Rajabi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Immanuel Kant written by Lucien Goldman is one of the most important books published during the 20th century. I explicate its various important aspects concentrating on its reproducing theme which is humanity, society, and their relationship with the universe within Kant’s philosophical thought. The relation of humans, society, and the universe is the most productive problem of modern philosophy; according to Goldman’s book, for Kant it is the most productive problem too. Goldman delineates how the relation of human, bourgeois society and the universe is the most focal point in Kant's philosophy, which has been pervaded throughout the chapters of the book, and I clarify it as well as Kant’s own account of the foregoing problem. Consequently, I recapitulate how most of the following philosophies are differentiated from this problem in addition to the next particular problems during the 19th and early 20th centuries.